2006
DOI: 10.1179/136485906x78445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ELISA and dot blots for the serodiagnosis of neurocysticercosis, in children found to have single or multiple enhancing lesions in computerized tomographic scans of the brain

Abstract: Although human neurocysticercosis (NCC) is being increasingly recognized in children, diagnosis of the disease can be difficult, and the 'gold standard' criteria that indicate an unambiguous case have still to be established. In the present study, the performances of an ELISA and dot-blot assay, for the detection of antibodies against antigens from larval Taenia solium, were investigated and compared, using sera, from children aged 5-12 years, that were diluted to at least 1:400. Eighty of the subjects (20 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
(26 reference statements)
2
25
0
Order By: Relevance
“…Both tests gave similar sensitivity, viz., 89%; while ELISA had better specifi city, viz., 81%, than Dot Blot (73%). [17] In another study by Biswas et al, Dot-ELISA was found to be 56.25% sensitive and 92% specifi c, as compared to plate ELISA, which was 43.75% sensitive and 98% specifi c. [12] Jiang et al have observed confi rmed cases of neurocysticercosis showing 81.6% to 96.1% positive reactions in Dot-ELISA. [11] It is reported that sensitivity and specifi city of Dot ELISA generally vary from 56.25% to 97.61% and from 90.6% to 92% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both tests gave similar sensitivity, viz., 89%; while ELISA had better specifi city, viz., 81%, than Dot Blot (73%). [17] In another study by Biswas et al, Dot-ELISA was found to be 56.25% sensitive and 92% specifi c, as compared to plate ELISA, which was 43.75% sensitive and 98% specifi c. [12] Jiang et al have observed confi rmed cases of neurocysticercosis showing 81.6% to 96.1% positive reactions in Dot-ELISA. [11] It is reported that sensitivity and specifi city of Dot ELISA generally vary from 56.25% to 97.61% and from 90.6% to 92% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…solium cysticerci crude soluble extract (CSE) antigen was prepared (Kaur et al 1996;Mandal et al 2006) and subjected to SDS-PAGE (Lamelli 1970). Antigenic fraction corresponding to standard molecular mass marker fraction of 20-24 kDa was eluted out (Plancarte et al 1994) from the gel by an electro eluter (BIORAD Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nearly two-thirds of the Indian patients have single lesion disease, therefore, there is need to identify the serodiagnostic tests with high sensitivity and specificity which can detect single lesion disease as well as multilesion disease with equal efficacy and high specificity (Rajshekhar and Chandy 1997;Prabhakar et al 2004). The present study was aimed to evaluate the efficacy of Tso cysticercus LMM antigen fraction (20-24 kDa) by ELISA and dot blot for the diagnosis of NCC in children and to compare the results of the present study with our previous study conducted in the same samples with the use of crude soluble extract (CSE) antigen (Mandal et al 2006). An attempt was also made to correlate the results of antibody response with radiological findings (single vs. multiple lesions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity was less for single lesions (52)and for calcified lesions (2;2;53-56). A comparative study of enzyme-linked immunosorbent assay (ELISA) and dotblot assay in children found that both were more sensitive in cases with multiple brain lesions (100%) than in those with a single lesion (87%) (5). The sensitivity of antibody detecting EITB assays is not better with the use of CSF samples as compared with serum samples (55).…”
Section: Laboratory Tests For Diagnosis Of Nccmentioning
confidence: 99%